Relationship between the structure, function and endothelial damage, and vascular ageing and the biopsychological situation in adults diagnosed with persistent COVID (BioICOPER study). A research protocol of a cross-sectional study - Gómez-Sánchez, Leticia; Tamayo-Morales, Olaya; Suárez-Moreno, Nuria; Bermejo-Martín, Jesus F.; Domínguez-Martín, Andrea; Martín-Oterino, José A.; Martín-González, José I.; González-Calle, David; García-García, Ángel; Lugones-Sánchez, Cristina; González-Sánchez, Susana; Jiménez-Gómez, Raquel; et al. (Frontiers in Physiology, 2023)
Background: SARS-CoV-2 infection affects the vascular endothelium, which mediates the inflammatory and thrombotic cascade. Moreover, alterations in the endothelium are related to arterial stiffness, which has been established as a marker of cardiovascular disease. The objective of this study is to analyse how the structure, vascular function, vascular ageing and endothelial damage are related to the biopsychological situation in adults diagnosed with persistent COVID and the differences by gender.Methods: This cross-sectional, descriptive, observational study will be carried out in the Primary Care Research Unit of Salamanca (APISAL) and in the BioSepsis laboratory of the University of Salamanca. The sample will be selected from the persistent COVID monographic office at the Internal Medicine Service of the University Hospital of Salamanca, and from the population of subjects diagnosed with persistent COVID in the clinical history of Primary Care.Through consecutive sampling, the study will include 300 individuals diagnosed with persistent COVID who meet the diagnosis criteria established by the WHO, after they sign the informed consent. Endothelial damage biomarkers will be measured using ELLA-SimplePlexTM technology (Biotechne). Their vascular structure and function will be analysed by measuring the carotid intimamedia thickness (Sonosite Micromax); the pulse wave and carotid-femoral pulse wave velocity (cfPWV) will be recorded with Sphygmocor System ® . Cardio Ankle Vascular Index (CAVI), brachial-ankle pulse wave velocity (baPWV) and ankle-brachial index will be analysed with Vasera VS-2000 ® . The integral assessment of the subjects with persistent COVID will be conducted with different scales that evaluate fatigue, sleep, dyspnea, quality of life, attention, nutrition state, and fragility. We will also evaluate their lifestyles (diet, physical activity, smoking habits and alcohol consumption), psychological factors, and cognitive deterioration, which will be gathered through validated questionnaires; moreover, physical activity will be objectively measured using a pedometer for 7 days. Body composition will be measured through impedance using an Inbody 230. Vascular ageing will be calculated with 10 and 90 percentiles of cfPWV and baPWV. Furthermore, we will analyse the presence of vascular injury in the retina, heart, kidneys and brain, as well as cardiovascular risk. Demographic and analytical variables will also be gathered.